Learner Autonomy: A Qualitative Inquiry into Indonesian Tertiary EFL Students' Voices - Daflizar Daflizar (Indonesian Research Journal in Education |IRJE|, 2021)
This study sought to explore Indonesian tertiary EFL students’ voices on learner autonomy. Specifically, it investigated the students’ conceptualization of the concept of learner autonomy, students’ perceptions of the benefits of learner autonomy, and their perceptions of the factors that hinder and support the development of learner autonomy. The study employed a qualitative design with a case study approach and involved 30 first-year students of two institutions of higher education in Jambi province, Indonesia. The data were collected using semi-structured interviews were analyzed using a thematic analysis following the steps proposed by Braun and Clarke (2006). The results revealed that the students had a limited understanding of the concept of learner autonomy. However, they believed that they would benefit from learner autonomy in terms of timing, learning effectiveness, and learning resources. The students also identified several hindering and supporting factors related to the development of learner autonomy. Practical implications for the Indonesian context are discussed.